2007
DOI: 10.1159/000107513
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of an Anti-Oxidant Intervention on Cardiomyocyte Expression of Adrenomedullin and Intermedin and their Receptor Components in Chronic Nitric Oxide Deficiency

Abstract: Background: Chronic inhibition of nitric oxide (NO) synthesis is associated with hypertension, myocardial oxidative stress and hypertrophic remodeling. Upregulation of the cardiomyocyte adrenomedullin (AM) / intermedin (IMD) receptor signaling cascade is also apparent in NO-deficient cardiomyocytes: augmented expression of AM and receptor activity modifying proteins RAMP2 and RAMP3 is prevented by blood pressure normalization while that of RAMP1 and intermedin (IMD) is not, indicating that the latter is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 51 publications
3
34
1
Order By: Relevance
“…21 However, it should be noted that the levels of the AM-related peptide intermedin, which is an agonist at the CGRP family of receptors (including the AM1 receptor), is also raised in a rat model of pressure overload. 25 Thus, AM1 receptor activity may be influenced by Ͼ1 agonist.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, it should be noted that the levels of the AM-related peptide intermedin, which is an agonist at the CGRP family of receptors (including the AM1 receptor), is also raised in a rat model of pressure overload. 25 Thus, AM1 receptor activity may be influenced by Ͼ1 agonist.…”
Section: Discussionmentioning
confidence: 99%
“…L-NAME-induced expression of AM and RAMP2 and RAMP3 was normalized by blood pressure normalization by hydralazine / hydrocholorothiazide [10] but not by antioxidant therapy with Tempol/ Vitamin C in the absence of blood pressure reduction [11], despite a similar reduction in the extent of cardiomyocyte hypertrophy indicating that pressureloading exerts a direct influence on expression of these genes independently of any ability to prevent cardiomyocyte hypertrophy. Unlike Tempol and Vitamin C [11], hydralazine and hydrochlorothiazide were unable to attenuate augmented IMD and RAMP1 expression [10] despite attenuation of cardiomyocyte hypertrophic parameters to a similar extent. This observation strongly supports a direct influence of oxidative stress upon expression of IMD and RAMP1, independent of any indirect influence associated with the contribution of oxidative stress to development of cardiomyocyte hypertrophy.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies in our laboratory indicate two important findings relating to cardiomyocytes subjected to chronic NO deficiency. Firstly, pressure loading and oxidative stress, exerted directly on the myocardium, both contribute to cardiomyocyte hypertrophy since antihypertensive therapy (smooth muscle relaxant hydralazine given concurrently with the diuretic hydrochlorothiazide, [10]) and antioxidant therapy in the absence of blood pressure reduction (Vitamin C in combination with Tempol, [11]) each partially, but incompletely, attenuated increased cardiomyocyte width despite normalizing blood pressure and cardiomyocyte membrane oxidant status, respectively. Furthermore, L-NAME induced expression of the hypertrophic markers, sk-α-actin and prepro-ET1, was abolished either by blood pressure lowering agents [10] or by antioxidants in the absence of blood pressure reduction [11]; in contrast, however, augmented expression of the natriuretic peptides, ANP and BNP, was normalized by blood pressure lowering [10] but not by antioxidants in the absence of blood pressure reduction [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the actions of ADM against ischemia-reperfusion injury are strongly influenced by pressure loading, 10 while expression of IMD is regulated by the extent of myocardial oxidative stress and is reduced by antioxidant therapy. 11 It has also been observed that IMD and ADM may be differentially affected by regulating factors; furthermore, the two peptides have distinct effects on arterial endothelial cells in vitro. 12 Although both IMD and ADM interact with all the three RAMPs, the ranked affinities between them differ: ADM has higher agonist activity with RAMP2 or RAMP3 than does IMD.…”
mentioning
confidence: 99%